Pola Promosi Destinasi Wisata Nusantara Melalui Words Of Mouth Marketing Dalam Akun Instagram Spektakel.id - Muda, Yogi Prima; Tanti, Dewi Sad (Universitas Mercu Buana, 2023)
This research aims to know the pattern of promotion of tourist destinations the archipelago through word of mouth marketing in social media. The use of Social Media in tourism is that can not terelakan again, even large countries tourism has account Instagram for branding, it describes that the effect social media for tourism branding so powerful. This encourages the birth of account instagram @spektakel.id. Word of Mouth Marketing is very important to introduce a brand to be discussed positively by the market being a target. The methods used in this research is qualitative, descriptive methods. The study also uses interviews with resource Admin account Instagram @spektakel.id, Word of Mouth Marketing expert and one of the followers. Elements of Word of Mouth Marketing that is used in this research was the talker, topic, tools, take a part, track and timing. Based on the results of research and discussion, Based on the results of research and discussion, it can be known that word of mouth marketing strategies used by account Instagram @spektakel.id managed to get people interested to follow the account of these and become Instagram talks by people a lot more and make known the archipelago and tourist destinations and crowded.